2020
DOI: 10.1111/jphp.13238
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine attenuates adjuvant-induced arthritis in rats by inhibiting synovial inflammation and restoring the Th17/Treg balance

Abstract: Objectives Evodiamine (Evo) possesses strong anti-inflammatory activity. In this study, we determine the antiarthritic effect of Evo. Methods Evo was administered to rats with adjuvant-induced arthritis (AA). We evaluated arthritis symptoms & histopathological changes and measured inflammatory cell infiltration, pro-inflammatory cytokine production and Th17 & Treg percentages in arthritic rats. Key findings Evo significantly improved the clinical signs of AA in rats, including decreases in paw swelling, the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The immune microenvironment of the RA synovium significantly differs from that of the synovium of healthy individuals [ 12 , 13 ]. Various inflammatory cells and abnormal cytokine release are found in the filtration fluid of patients with RA [ 14 , 15 ]. Rheumatoid factors are IgM antibodies secreted by synovial B cells that may identify the Fe segment of immunoglobulin and form immune complexes, release chemokines, and fix complements, thereby resulting in the collection of inflammatory cells in the joints of the affected patients [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immune microenvironment of the RA synovium significantly differs from that of the synovium of healthy individuals [ 12 , 13 ]. Various inflammatory cells and abnormal cytokine release are found in the filtration fluid of patients with RA [ 14 , 15 ]. Rheumatoid factors are IgM antibodies secreted by synovial B cells that may identify the Fe segment of immunoglobulin and form immune complexes, release chemokines, and fix complements, thereby resulting in the collection of inflammatory cells in the joints of the affected patients [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This also applies for AA [62][63][64]. RB alone has no effect on the IL-17A levels in plasma (Figure 5).…”
Section: Discussionmentioning
confidence: 67%
“…Wang et al (2019) have reported that the curcumin attenuates collagen-induced rat arthritis through apoptotic and anti-inflammatory effects. Researchers have reported that the evodiamine reduces adjuvant-induced arthritis in rats through the inhibition of synovial inflammation and restoring the Th17/Treg balance (Zhang et al 2020). Supplementation of telmisartan with etanercept attenuates anemia associated with rheumatoid arthritis in rats (Hasanin and Mohamed 2020).…”
Section: Discussionmentioning
confidence: 99%